Experimental Investigations on the Mechanical Characteristics of Natural Fiber Particle-Reinforced Polymer Composites under Cryogenic Environment. (24th August 2022) - Alshgari, Razan A.; Anandaram, Harishchander; Kistan, A.; Nisha, N.; Vel, V. M.; Anitha, G.; Wabaidur, Saikh Mohammad; Islam, M. A.; Alemayehu, Agonafir
Abstract : In the past few years, researchers have turned away from previous metals and minerals and more towards lightweight materials throughout addition to creating lightweight, better effective composites for special tasks. The composite materials were created by employing the most advantageous hand layup approach. To attain the aforementioned goals, the following limitations were implemented: at various levels, (i) coconut shell powder, (ii) walnut powder, and (iii) cryogenic treatment hours are all accessible. At 77 K, the laminated composite was put in a cryogenic chamber. Tensile, flexural, and interlaminar shear strengths were all tested mechanically. In comparison to 100  μ m coconut shell powder-based particle composites, 80  μ m walnut shell composites gave the maximum mechanical strength, while 10 wt% coconut shell powder and walnut and 80 wt% polyester also had a beneficial impact. The morphological behaviour of the particulate material was detected using a scanning electron microscope (SEM).